1999
DOI: 10.1093/emboj/18.5.1415
|View full text |Cite
|
Sign up to set email alerts
|

P1 ParA interacts with the P1 partition complex at parS and an ATP-ADP switch controls ParA activities

Abstract: The partition system of P1 plasmids is composed of two proteins, ParA and ParB, and a cis-acting site parS. parS is wrapped around ParB and Escherichia coli IHF protein in a higher order nucleoprotein complex called the partition complex. ParA is an ATPase that autoregulates the expression of the par operon and has an essential but unknown function in the partition process. In this study we demonstrate a direct interaction between ParA and the P1 partition complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
175
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(192 citation statements)
references
References 46 publications
15
175
2
Order By: Relevance
“…These interactions required magnesium in the gel and running buffer. Under these conditions, the two discrete complexes, corresponding to I ϩ B1 and I ϩ B2, are not observed, although the ParB complex migrates more slowly with increasing ParB concentrations (24). While the experimental conditions are not identical, it is possible, for example, that ParA is recruited only to a partition complex that contains two ParB dimers (complex I ϩ B2 or higher), perhaps explaining a requirement for high concentrations of ParB.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…These interactions required magnesium in the gel and running buffer. Under these conditions, the two discrete complexes, corresponding to I ϩ B1 and I ϩ B2, are not observed, although the ParB complex migrates more slowly with increasing ParB concentrations (24). While the experimental conditions are not identical, it is possible, for example, that ParA is recruited only to a partition complex that contains two ParB dimers (complex I ϩ B2 or higher), perhaps explaining a requirement for high concentrations of ParB.…”
Section: Discussionmentioning
confidence: 94%
“…We reported recently that ParA interacts with ParB on the partition complex (24). The nature of this interaction is dependent on ParB concentration.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It has since been shown that ParA assembles onto the partition complex at parS and that this interaction is completely dependent on ATP, whereas the repressor activity of ParA prefers the ADP-bound form. These observations have led to the proposal that an ATP-ADP switch controls ParA entry into two separate pathways in which ParA plays separate roles (Bouet & Funnell 1999).…”
Section: E Coli Plasmid P1 and F Factormentioning
confidence: 99%